The Effect of Employee, Management, Working Environment, and Safety Culture on Occupational Healthy and Safety Performance: A Case Study in an Oil and Gas Company in Indonesia - Sugiono, Nana; kusrini, elisa; Ali, Juhary; Miranda, Suci (International Journal of Integrated Engineering, 2020)
The level of workplace accidents, particularly in large companies such as the oil and gas industry, is crucial to be overcome. Encouragement of occupational health and safety (OHS) is one priority of strategies that must be carried out in the implementation of work in the workplace. This study aims to determine the impact of employee, management, work environment, and safety culture on occupational health and safety (OHS) performance. This paper also discusses the influence of moderating safety culture on the independent variables towards the achievement of safety performance. Using questionnaires to 220 respondents, findings indicate that the safety performance is significantly affected by employee, management, working environment, and safety culture. There are 19 attributes of 4 variables evaluated. All attributes have significantly influenced the OHS performance but 4 attributes of management variables. They are pre and post task safety review, safety work procedure, incident investigation, and detection and monitoring.  The research provides the empirical evidence on the significance of Safety Culture as moderator. The safety culture moderates the positive relationship between management and OHS performance as well as working environment and OHS performance. Conversely, safety culture does not influence the positive relationship between employee and the OHS.